MANUFACTURE OF ACTIVE CARBON TABLETS FROM SALACCA (SALACCA ZALACCA) SEEDS AS ANTI-DIARY TREATMENT - Christica Ilsanna Surbakti; Bunga Rimta Barus (JBIO: jurnal biosains (the journal of biosciences), 2022)
Salak seeds (Salacca zalacca) used to be considered as waste that is not useful and just thrown away. Now with advances in technology, some of the by-products of salak seeds can be processed into more economical products such as activated carbon which can be used as a treatment for diarrhea because it acts as an adsorbent. The method used to make activated carbon tablets is the wet granulation method with 2 kinds of formulas. The physical properties of the tablets were tested, including weight uniformity, hardness, friability and tablet disintegration time. Pharmacological testing on this activated carbon tablet which is used for the treatment of diarrhea will be tested on rats given orally and observed for 3 days.and the maximum result is the addition of 250 mg of activated carbon where the weight of the feces is reduced by up to 30%